The emergence and challenges of blockchain technology in business and IoT applications - Suyatna, I. Putu Ngurah; Mohamed, Yusaini Hisham; Abbas, Mohd Saleh; Ismail, Albert Feisal; Magiman, Mohamad Maulana; Mohd Yunus, Yusmi (IEEE, 2023)
As we can see nowadays Blockchain is gaining popularity among us via media and press in various domains, especially in Banking and payment-related stuff. At the business level, this blockchain concept is about to set a new standard as it is going to be used as a foundation of a very new technology emerging that actually deals with security and internet immutability. Here we will also discuss the challenges being faced when implementing blockchain and we will also cover new areas where it is being implemented. In the end, we really hope that our research will help others to make any sort of decision if they are willing to work on the blockchain and want to invest in IoT.